Hydrological Outlook UK: an operational streamflow and groundwater level forecasting system at monthly to seasonal time scales. Issue 16 (10th December 2017) - Prudhomme, Christel; Hannaford, Jamie; Harrigan, Shaun; Boorman, David; Knight, Jeff; Bell, Victoria; Jackson, Christopher; Svensson, Cecilia; Parry, Simon; Bachiller-Jareno, Nuria; Davies, Helen; Davis, Richard; et al.
ABSTRACT: This paper describes the development of the first operational seasonal hydrological forecasting service for the UK, the Hydrological Outlook UK (HOUK). Since June 2013, this service has delivered monthly forecasts of streamflow and groundwater levels, with an emphasis on forecasting hydrological conditions over the next three months, accompanied by outlooks over longer time horizons. This system is based on three complementary approaches combined to produce the outlooks: (i) national-scale modelling of streamflow and groundwater levels based on dynamic seasonal rainfall forecasts, (ii) catchment-scale modelling where streamflow and groundwater level models are driven by historical meteorological forcings (i.e. the Ensemble Streamflow Prediction, ESP, approach), and (iii) a catchment-scale statistical method based on persistence and historical analogues. This paper provides the background to the Hydrological Outlook, describes the various component methods in detail and then considers the impact and usefulness of the product. As an example of a multi-method, operational seasonal hydrological forecasting system, it is hoped that this overview provides useful information and context for other forecasting initiatives around the world.